2020
DOI: 10.5433/1679-0359.2020v41n5p1517
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of corn phenological stages using NDVI from OLI and MODIS sensors

Abstract: Images from MODIS and OLI sensors were used. Corn phenology was evaluated through NDVI. Data were validated by model identity testing. NDVI can help identify problems in corn crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Figure 2B shows the significant relationships between the different growth stages and NDVI values. The data corroborate those of Wang et al (2016), Alvino et al (2020 and Venancio et al (2020), to which the behavior of the NDVI obtained via satellite images throughout the development cycle of maize was evaluated. These authors found a rapid increase in NDVI values at the beginning of the cycle, thus confirming the results found between the stages V4 and V9.…”
Section: Resultssupporting
confidence: 87%
“…Figure 2B shows the significant relationships between the different growth stages and NDVI values. The data corroborate those of Wang et al (2016), Alvino et al (2020 and Venancio et al (2020), to which the behavior of the NDVI obtained via satellite images throughout the development cycle of maize was evaluated. These authors found a rapid increase in NDVI values at the beginning of the cycle, thus confirming the results found between the stages V4 and V9.…”
Section: Resultssupporting
confidence: 87%
“…In addition, the type of input predictors for both models were evaluated to fit the predictive models using high-resolution data. The study demonstrates the potential of using spectral bands as an alternative approach to the common crop yield forecast based on VIs [23,[54][55][56]. The spatial variability of the fields was mapped for the range of yield data values across all fields over the sugarcane growing seasons.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, elevated values of the Normalized Difference Vegetation Index (NDVI) indicated enhanced photosynthetic capacity and the increased uptake of essential soil nutrients, such as nitrogen. Consequently, this was reflected in amplified grain production within corn crops, as demonstrated by previous studies [27][28][29][30]. Furthermore, similar outcomes could be attained by employing unmanned aerial vehicles (UAVs) equipped with high-resolution multispectral passive sensors for remote sensing.…”
Section: Discussionmentioning
confidence: 54%